My perfect pony - Goldsack, Gaby; White, Michelle (Parragon Pub. UK, 2006)
Pepper, feeling low because the other ponies laugh at him when he tries to practice for an upcoming horse show, has a dream that shows him why he is the perfect pony for his owner, Lucy, which gives him confidence to try his best